KINERJA DAN NILAI TAMBAH AGROINDUSTRI SAGU AREN DI KABUPATEN LAMPUNG SELATAN - Abu Haris Husain; Ktut Murniati; Adia Nugraha (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
This study aimed to analyze the raw material procurement system based on six components, the performance and the added value of the palm sago agro-industry in Natar subdistrict of South Lampung Regency. The research was a case study in which location was chosen purposively in four Sago Aren Agroindustries by considerating that there were only four agro-industries that were still actively producing sugar palm sago in that area. The reseach data collection was conducted in March - April 2018 and analyzed by qualitative and quantitative descriptive and added value analysis. The results showed that the six components of raw material procurement namely time, place, quality, organization, quantity, and price in Sago Aren of Adi Putra, Oblak, and Surahmat Agroindustries were appropriate because they have been in line with expectations. There was still a component of material procurement standards that have not been matched or did not in line with the expectation in Kartim Agroindustry namely quantity. Production performance in the Sago Aren Agroindustries could be classified as good, because four of the five indicators in production performance namely productivity, capacity, quality, and speed of delivery were appropriate, while indicators of flexibility in the four sago palm agroindustry was not optimal, and the four sago palm agroindustry was feasible because it provided positive added value. Key words: sagu aren, performance, value added